2021
DOI: 10.3389/fimmu.2021.613591
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lipids in Morphogenesis of T-Cell Microvilli

Abstract: T cells communicate with the environment via surface receptors. Cooperation of surface receptors regulates T-cell responses to diverse stimuli. Recently, finger-like membrane protrusions, microvilli, have been demonstrated to play a role in the organization of receptors and, hence, T-cell activation. However, little is known about the morphogenesis of dynamic microvilli, especially in the cells of immune system. In this review, I focus on the potential role of lipids and lipid domains in morphogenesis of micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…While we focus on sensory neurons, microvilli are present throughout the body on a wide variety of cell types, including epithelial and immune cells (Cebecauer, 2021). For each cell type, the microvilli can be adapted to the particular niche through modifications to the width and length of the actin core, and to the complement of actin‐binding proteins, membrane proteins, and surrounding extracellular matrix components.…”
Section: Selected Types Of Microvillated Cellsmentioning
confidence: 99%
“…While we focus on sensory neurons, microvilli are present throughout the body on a wide variety of cell types, including epithelial and immune cells (Cebecauer, 2021). For each cell type, the microvilli can be adapted to the particular niche through modifications to the width and length of the actin core, and to the complement of actin‐binding proteins, membrane proteins, and surrounding extracellular matrix components.…”
Section: Selected Types Of Microvillated Cellsmentioning
confidence: 99%
“…For example, scanning electron microscopy micrographs have demonstrated that finger-like membrane protrusions reminiscent of microvilli dominate the surface of lymphocytes 36 38 . T-cell microvilli are dynamic structures ~100 nm in diameter and 0.5–5 µm long 39 , 40 . Although less well understood on immune cells, tips of microvilli can potentially accumulate membrane receptors in domains with a diameter ~100 nm, analogous to signaling receptors and channels on epithelial and sensory cells 41 .…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that microvilli, finger‐like membrane protrusions on cells, play a role in the organization of signalling proteins and are important for T‐cell recognition and activation [36–38]. We found that the microvilli and lamellipodia on the surface of lymphocytes became more obvious after CIK culture (Fig.…”
Section: Discussionmentioning
confidence: 63%